Effect of Work Environment, Workload, and Work Stress on Employee Performance at PT. Inti Naratama Karya - Daniel Jonathan; Pujiarti Pujiarti; Andy (Primanomics : Jurnal Ekonomi & Bisnis, 2024)
Writing thesis This aim For know influence environment work, burden work, and stress Work to performance employee at PT. Inti Naratama Karya. Study This done with spread questionnaire, meanwhile For method study use method descriptive. From the results study obtained equality multiple linear analysis Y = 46.010 + 0.249 X1 – 0.582 X2 + 0.062 X3 + e and results coefficient correlation environment Work own negative correlation with level connection weak to performance employee that is of 0.483, load Work own negative correlation with level connection very weak to performance employee that is of – 0.690, stress Work own negative correlation with level connection very weak to performance employee that is of -0.458. Based on results test hypothesis t test was obtained tcount of 1.251(X1), -3.849 (X2), and 0.341 (X3), with ttable amounting to 1.68709 obtained from ttable distribution For df = 40 – 3 and level of significance is 0.05, in other words Ho is accepted and Ha is rejected. Is known mark F test is obtained results amounting to 11.922 > 2.87. From the results t value and F value , then can concluded that Ho was rejected and Ha accepted, which means environment work, burden work, and stress Work influential positive And significant to performance employee at PT Inti Naratama Karya.